Active Component of Antrodia cinnamomea Mycelia Targeting Head and Neck Cancer Initiating Cells through Exaggerated Autophagic Cell Death. (12th June 2013) - Chang, Ching-Wen; Chen, Chien-Chih; Wu, Meng-Ju; Chen, Yu-Syuan; Chen, Chin-Chu; Sheu, Sen-Je; Lin, Ting-Wei; Chou, Shiu-Huey; Lin, Shu-Chun; Liu, Chung-Ji; Lee, Te-Chang; Huang, Chih-Yang; et al.
Abstract : Head and neck squamous cell carcinoma (HNSCC) is a highly lethal cancer. Previously, we identify head and neck cancer initiating cells (HN-CICs), which are highly tumorigenic and resistant to conventional therapy. Therefore, development of drug candidates that effectively target HN-CICs would benefit future head and neck cancer therapy. In this study, we first successfully screened for an active component, named YMGKI-1, from natural products of Antrodia cinnamomea Mycelia (ACM), which can target the stemness properties of HNSCC. Treatment of YMGKI-1 significantly downregulated the aldehyde dehydrogenase (ALDH) activity, one of the characteristics of CIC in HNSCC cells. Additionally, the tumorigenic properties of HNSCC cells were attenuated by YMGKI-1 treatment in vivo . Further, the stemness properties of HN-CICs, which are responsible for the malignancy of HNSCC, were also diminished by YMGKI-1 treatment. Strikingly, YMGKI-1 also effectively suppressed the cell viability of HN-CICs but not normal stem cells. Finally, YMGKI-1 induces the cell death of HN-CICs by dysregulating the exaggerated autophagic signaling pathways. Together, our results indicate that YMGKI-1 successfully lessens stemness properties and tumorigenicity of HN-CICs. These findings provide a new drug candidate from purified components of ACM as an alternative therapy for head and neck cancer in the future.